Mobile systems - Groves, Ian (BT telecommunications series, 1998)
This book provides an authoritative overview of current mobile systems, both cellular and cordless, and examines their evolution towards the next generation of systems. It focuses on the key issue of Radio Spectrum and its management and discusses important environmental and safety issues, addressing radio interference and the environmental impact of mobile base stations, as well as the alleged health hazards associated with the use of mobile phones. Satellite systems and the application of cellular techniques to aeronautical applications for the travelling customer are discussed, and the book ends with an exploration of the latest developments in the next generation of systems.